Interview with Eva D. Bahovec - TWSC Staff (Kasarinlan: Philippine Journal of Third World Studies, 2008)
The Symposium of the International Association of Women Philosophers held at the University of Wien, Austria in September 1995 became the occasion for the interviewee to meet Dr. Eva Bahovec of the Center for Women's Studies, University of Lubljana/ Slovenia and co-editor of the journal Women's Studies and Feminist Theories published in her home country and language. Here, in this hitherto unpublished interview, Dr. Bahovec recalls the democratic changes that swept her country and how these affected the growth of feminist groups in Slovenia including the birth of several feminist joumals.
Keywords: Feminism; Social Movements